Ma, performing the White, Afrikaner Woman back to self - Viljoen, Kanya (Department of Drama, 2021)
This research project seeks to understand myself and my position within South Africa. The position of a young, white, Afrikaner woman. This is a position that, one could argue, inherently carries a sense of a tragedy within it. The project seeks to understand how the elements of tragedy, such as conflict and transgression, in turn, can be employed in my performance-making practice to question the very identity I hold. The research recounts the histories and narratives that have been constructed around the white, Afrikaner woman in South Africa, specifically with regards to a paradoxical positionality in the white, Afrikaner woman's ‘role' in the construction of the white, Afrikaner identity. Furthermore, it seeks to understand how narratives and histories embed themselves within nostalgic objects that centralise around the white, Afrikaner woman. Utilising the very narratives and objects that have constructed the white, Afrikaner woman, I create performances that seek to use these objects, including the Afrikaans language itself, and my own body, to transgress and abject the notions of the border, my body, and subjectto-object and object-to-subject relationality within this very identity I hold. During these performances and moments of transgression and abjection, I argue that liminal moments in which I can re-imagine myself are encountered and experienced. These moments are often fleeting and exist as attempts at re-imagining myself, but so too hold the ability to affect and shift something within my own understanding of self. Finally, the research seeks to understand how these very positionalities and performances are related to the tragic and tragedy; catastrophe and the notion of the wreckage, as theorised by Walter Benjamin (1968), Hans-Thies Lehmann (2016) and Nelson Maldonado-Torres (2016) and how these theories might speak to an understanding of my identity and positionality in South Africa, my understanding of self.